Twentieth century women's literature: exploration of female-identity and expressions of independence, autonomy and self-assertion - Khan, Raisa Tamanna (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2012.